2021
DOI: 10.1038/s41598-021-85824-z
|View full text |Cite
|
Sign up to set email alerts
|

Group contribution and atomic contribution models for the prediction of various physical properties of deep eutectic solvents

Abstract: The urgency of advancing green chemistry from labs and computers into the industries is well-known. The Deep Eutectic Solvents (DESs) are a promising category of novel green solvents which simultaneously have the best advantages of liquids and solids. Furthermore, they can be designed or engineered to have the characteristics desired for a given application. However, since they are rather new, there are no general models available to predict the properties of DESs without requiring other properties as input. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 128 publications
0
19
0
Order By: Relevance
“…A DES is actually an associating mixture of at least two components consisting of a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD), while an IL is a pure component involving ionic interactions between its constituent cations and anions. In this manner, they are theoretically quite different green solvents, having some similarities in their general behavior [12].…”
Section: Introductionmentioning
confidence: 97%
“…A DES is actually an associating mixture of at least two components consisting of a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD), while an IL is a pure component involving ionic interactions between its constituent cations and anions. In this manner, they are theoretically quite different green solvents, having some similarities in their general behavior [12].…”
Section: Introductionmentioning
confidence: 97%
“…This highlights the need for systematic studies of DESs to improve their fundamental understanding and to ultimately create predictive models. 64 As such, the present review will primarily focus on computational efforts aimed at providing predictions and insight into the structure-property relationship of Type III DESs.…”
Section: Composition Of Type III Deep Eutectic Solventsmentioning
confidence: 99%
“…However, optimizing DES mixtures towards a specific application can become quickly overwhelming when using an uneducated trial‐and‐error approach that may easily override any potential advantages provided by the solvent. This highlights the need for systematic studies of DESs to improve their fundamental understanding and to ultimately create predictive models 64 . As such, the present review will primarily focus on computational efforts aimed at providing predictions and insight into the structure–property relationship of Type III DESs.…”
Section: Deep Eutectic Solventsmentioning
confidence: 99%
“…19,20 This has prompted the use of theoretical and computational methods in studying the properties and predicting new possible DESs. These methods include, but are not limited to, molecular dynamics simulations, 21−26 classical thermodynamic models such as group contribution methods, 19,27,28 and quantum chemical calculations. 29−32 While some group contribution methods (COSMO-RS, UNIFAC, and others) are being used to predict properties of possible new DESs, a significant portion of publications related to these methods focus on correlating experimental data from type III DESs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although the total number of possible DESs is unknowable, and will likely to remain so until the community has come to an agreement on how to classify a solvent as a DES, current works have demonstrated that the growing amount of existing DESs is causing a comprehensive experimental mapping of their properties and behavior to be less and less feasible. , This has prompted the use of theoretical and computational methods in studying the properties and predicting new possible DESs. These methods include, but are not limited to, molecular dynamics simulations, classical thermodynamic models such as group contribution methods, ,, and quantum chemical calculations. While some group contribution methods (COSMO-RS, UNIFAC, and others) are being used to predict properties of possible new DESs, a significant portion of publications related to these methods focus on correlating experimental data from type III DESs …”
Section: Introductionmentioning
confidence: 99%